1999
DOI: 10.1097/00004714-199904000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor Performance of Long-Term Benzodiazepine Users Before, During, and After Benzodiazepine Discontinuation

Abstract: Long-term (mean, 8 years) users of benzodiazepines (BZs) were administered a small battery of cognitive tests on three occasions (before BZ taper, and 5 and 12 weeks post taper) as part of their BZ discontinuation program. Ninety-six patients had 5-week and 77 patients had 12-week data. For taper successes, BZ-free status was confirmed by weekly BZ plasma level determinations. Age and education, as well as baseline test scores, were used as covariates for all data analyses. Patients who successfully tapered of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 20 publications
3
21
0
Order By: Relevance
“…However, another study reported tolerance to the acute amnesic effects of alprazolam after chronic use [40]. A major concern is that loss of memory associated with benzodiazepine use may be lasting, even after treatment discontinuation [62, 63], although other studies reported improved cognitive functioning after discontinuation with increased speed and accuracy of information processing, improved reaction time and working memory [50, 6466]. Collectively, clinical data do not support the existence of tolerance to benzodiazepine-induced cognitive impairments.…”
Section: The Development Of Benzodiazepine Tolerancementioning
confidence: 99%
“…However, another study reported tolerance to the acute amnesic effects of alprazolam after chronic use [40]. A major concern is that loss of memory associated with benzodiazepine use may be lasting, even after treatment discontinuation [62, 63], although other studies reported improved cognitive functioning after discontinuation with increased speed and accuracy of information processing, improved reaction time and working memory [50, 6466]. Collectively, clinical data do not support the existence of tolerance to benzodiazepine-induced cognitive impairments.…”
Section: The Development Of Benzodiazepine Tolerancementioning
confidence: 99%
“…However, clinical treatment often extends beyond 3 weeks (e.g., years), increasing the associated morbidity and mortality (Hampton et al, 2014; Tamblyn et al, 2005; Pariente et al, 2008). Conversely, discontinuation of BZPs in long-term users is generally associated with an improvement in cognitive function, with no significant adverse effects (Kitajima et al, 2012; Rickels, 1999). …”
Section: Introductionmentioning
confidence: 99%
“…Long-term benzodiazepine (BDZ) use leads to tolerance and dependence, affecting also adversely users' cognitive functioning (Ashton, 2005;Golombok et al, 1988;Rickels et al, 1999;Stewart, 2005). Among the available pharmacological means the most efficacious are, thus far, the gradual rather than the abrupt discontinuation of BDZ and the use of carbamazepine as an adjunctive medication (Denis et al, 2006).…”
Section: Introductionmentioning
confidence: 99%